69.7k views
2 votes
Simplify the expression completely. 7b+3(4b−2)+6÷3

User Bhamby
by
5.6k points

2 Answers

3 votes

Answer:

19b - 4

Explanation:

Distribute the 3 to (4b - 2), like so:

3(4b - 2)

12b - 6

→ 7b + 12b - 6 +6 ÷ 3

Add like terms:

→19b - 6 + 6 ÷ 3

Following PEMDAS, you divide 6 by 3 first:

→19b - 6 + 2

Add like terms:

→19b - 4

User Gurbieta
by
6.5k points
5 votes

Answer:

19b-4

Explanation:

7b+3(4b-2)+6÷3

Bracket comes first so we distribute 3 over the terms in the bracket

= 7b + 12b -6 +6 ÷ 3

First we solve division

= 7b + 12b -6 +6 ÷ 3

= 7b + 12b -6 +2

= (7b+12b)+(-6+2)

= 19b -4

This can't be simplified further as it can't be solved anymore

User Tioma
by
5.7k points